Latent Transitions of Learning Interests among Kindergarteners in Hakka Bilingual Teaching Programs - Chung-Chin Wu (MDPI AG, 2023)
The profiles of kindergarteners' learning interests in Hakka bilingual teaching programs are unclear and the effects of these programs on the transition of such interests over the long term are under investigation. This study analyzed the learning interest profiles of 112 kindergarteners (data gathered by kindergarten teachers) enrolled in immersion/non-immersion Hakka bilingual programs in Taiwan. Latent transitions in these profiles were analyzed based on pre- and post-implementation data. The results showed that two different subgroups were identified based on the kindergarteners' learning interest profiles before and after the implementation of the Hakka bilingual program. The pre-implementation subgroups contained the "moderate situational and low-to-moderate individual interest" and the "high situational and moderate-to-high individual interest" profiles. Post-implementation subgroups consisting of "moderate-to-high situational and moderate individual interest" and "high situational and individual interest" profiles were identified. Moreover, four patterns of transition in the kindergarteners' learning interest profiles were uncovered: (1) a slight increase in both learning interests, (2) a significant increase in both learning interests, (3) a slight regression in both, and (4) a maintenance of situational interest coupled with a slight increase in individual interest. Lastly, the non-immersion Hakka program showed significant and more positive effects on the "moderate situational and low-to-moderate individual interest" profile subgroup compared to the equivalent group from the Hakka immersion program. These results provide new evidence complementing previous findings reached via different analytical approaches and contribute to the overall conclusion that bilingual programs improve learning outcomes.